Metal Removal Using Fe3O4-Chitosan Nanoparticles for Environmental Applications - Leandro-Silva, Emerson [UNESP]; Silveira, Maria L.D.C. [UNESP]; Pipi, Angelo R.F. [UNESP]; Piacenti-Silva, Marina [UNESP]; Magdalena, Aroldo G. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2024)
Environmental contamination with toxic elements due to increasing anthropogenic activities is of concern because of its direct effects on health and the environment. To help in mitigate this problem, in this study, Fe3O4 and Fe3O4-chitosan nanoparticles were synthesized, characterized and used as adsorbents to remove metal ions from wastewater samples. The nanoparticles were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, zeta potential, and transmission electron microscopy (TEM), which confirm that functionalization of the chitosan on the Fe3O4 surface was efficient. Inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis determined the metal concentrations in the wastewater samples. The metal adsorption from wastewater showed that Fe3O4-chitosan nanoparticles had a removal percentage above 90% for the metals barium, iron, manganese, and zinc. For aluminum, the removal percentage was about 60%.
Remoção de Metais Usando Nanopartículas de Fe3O4-Quitosana para Aplicações Ambientais
Keywords: chitosan; metal removal; Nanoparticles; wastewater